Automatic calibration system for micro-displacement devices. (12th July 2018) - Shih, Hung-Ta; Wang, Yung-Cheng; Shyu, Lih-Horng; Tung, Pi-Cheng; Chang, Chung-Ping; Jywe, Wen-Yuh; Chen, Jia-Hong
Abstract: With the advanced development of micro-displacement technology, the correlated applications of piezo transducers (PTs) have been widely implemented in the precision industry. The calibration of significant parameters of PTs, including nonlinearity and error due to hysteresis, must be determined and verified before their employment. Hence, the development of an automatic calibration system which can ensure quality and detect any decline or damage before the utilization of the PT is the primary goal. A self-developed system based on the international specification of ASTM-E2309 for the automatic calibration of PTs is constructed in this study. The system bears the feature of a common optical path and a resolution of sub- m m order. The testing results illustrated that the repeatability of the proposed Fabry–Pérot interferometer is within 15 nm. In accordance with the experimental arrangement of synchronic measurement, the comparison results between the self-developed and the commercial interferometer indicate that the differences of the maximum nonlinearity and maximum hysteresis error are less than 1%. By the presented correct method, the maximum nonlinearity error can be minimized to 0.5% and the maximum hysteresis error will be reduced to 1.1%.